Frequency, Timing and Costs of Intraspecific Nest Parasitism in the Common Eider - Robertson, G.J.; Watson, M.D.; Cooke, F. (University of California Press, 1992)
Intraspecific nest parasitism was studied in the Hudson Bay race of the Common Eider (Somateria mollissima sedentaria), near Churchill, Manitoba (58 24'N, 94 24'W). Nest parasitism was detected by three methods: (1) multiple eggs laid in the same nest on a single day, (2) eggs laid before or after the host's clutch was laid, and (3) large within clutch variances in egg size and color. It was determined that 42.4% (n = 153) of completed clutches were parasitized. Parasitic eggs were laid significantly earlier in the host's laying sequence than expected by chance: 65% of parasitic eggs were laid on the first two days of laying. Number of parasitic eggs laid, as a proportion of all eggs, did not change significantly throughout the laying period. The probability of parasitic and host eggs hatching was not significantly different from that in unparasitized nests. Hosts did not reduce their clutch size in response to parasitism, when data were controlled for initiation date, nor did they hatch any fewer of their own young for a given clutch size than unparasitized nests. Parasitized nests were found in areas with higher densities (number of neighbors within 10 m) at initiation. Parasitism in this species does not appear to be a salvage strategy and may be part of a mixed or conditional strategy.